Dampak Pandemi Covid-19 Terhadap Perkembangan Psikososial Remaja - IGA Dewi Purnamawati; Siti Nurhayati (Jurnal Pengabdian Kepada Masyarakat Kalam, 2022)
The Covid 19 pandemic has been happening in Indonesia for a long time, starting from March 2020 to March 2022, for approximately 2 years, we all felt together with the impact of the pandemic. The impact of the Covid-19 pandemic on the world of education is felt by teenagers. Changes in offline learning methods to online, studying at home all day, lots of assignments, and not being able to meet friends, all of which can interfere with adolescent psychosocial development, for that we need a solution by increasing adolescent knowledge by providing health education. This community service activity aims to increase adolescent knowledge about adolescent psychosocial development, the impact of the pandemic, and solutions that adolescents must take to continue their healthy adolescent psychosocial development. This health education activity is carried out online. Participants in this activity were 24 high school students from several provinces, namely West Java, DKI Jakarta, Central Java, and South Sumatra. Evaluation of activities is carried out by conducting a post-test with the results that 70% of students can answer correctly the questions given. The enthusiasm of the youth and the involvement of the Pasar Rebo Nursing Academy students in this PKM activity made the activity run smoothly and successfully. A follow-up plan is needed to increase youth knowledge about healthy adolescent development towards a strong young generation.